What triggers the use of mIM service provider's sequel O2O service extensions? - ShinYoung Hwang; Kim Seongcheol (International Telecommunications Society (ITS), 2017)
Advancements in mobile technology have created a new paradigm that transform people's daily lives. Through smart wireless devices that provide Internet access anytime and anywhere, users have more opportunities for real-time communication, entertainment, and information consumption. One of the most widely accepted and experienced application is the mobile instant messaging (mIM) service that enables users to exchange highly synchronized one-on-one or one-to-many communication (Wallace, 2012). The benefits of mIM are seen through the large user bases that mIM service providers hold. As of January 2017, WhatsApp and Facebook Messenger had 1,000 million monthly active users (MAU) followed by QQ mobile (877 million MAUs) and WeChat (846 million MAUs). Indeed, Korea's mIM applications, Line and KakaoTalk, are also listed as one of the top ten most used mIM applications with 218 million MAUs and 49 million MAUs, respectively (Statista, 2017). Although mIM services experience sluggish growth in active monthly users, the saturated market is still anticipated to possess a total of 3.8 billion registered mIM users by the end of 2019 (Radicati Group, 2016).
Keywords: 330